Markers of inflammation in obese pregnant women: Adenosine deaminase and high sensitive C - reactive protein - Grisilda Vidya Bernhardt; Pooja Shivappa; Kavitha Bernhardt; Sujatha Bhat; Janita R.T. Pinto; Malay Jhancy; Suresh Kumar (Elsevier, 2022)
Introduction: The worldwide increase in the prevalence of obesity over the years has emerged as a global health concern. The growing rate of obesity in women of child bearing age is particularly a matter of concern. Obesity is considered a risk factor that predisposes an individual to a proinflammatory state through the release of the inflammatory mediators. Recent studies have shown a positive correlation between the severity of inflammation and an increase in adenosine deaminase (ADA) and high sensitivity C- reactive protein (hs-CRP). Obese pregnancy women are at a higher risk for developing inflammation-mediated pregnancy complications like gestational diabetes, preeclampsia, and preterm delivery. Considering the fact that pregnancy, obesity and inflammation are closely linked, this study evaluated the inflammation associated with obesity during pregnancy by estimating changes in ADA and hs-CRP. Materials and methods: The current study aimed to evaluate the levels of inflammation in obese pregnant women compared to non-obese pregnant women by correlating BMI with levels of ADA / hs-CRP. The study also aimed to examine the change in ADA and hs-CRP levels with gestational age (between the 1st and the 3rd trimester) in obese pregnant women as compared to non-obese pregnant women. We also examined whether changes in the levels of ADA correlate with changes in the levels of hs-CRP particularly in obese pregnant women.Blood samples were collected from obese and non-obese pregnant women. ADA activity and hs-CRP levels were estimated by biochemical assays. BMI was evaluated in the 1st trimester and those women with BMI > 30 kg/m2were considered as obese. Thirty subjects were included in each of the two groups. Results: ADA and hs-CRP levels were significantly higher in obese pregnant women in both the 1st and 3rd trimesters compared to non-obese participants (P value<0.05). Statistically significant higher values of ADA and hs-CRP were seen in obese participants in the 3rd trimester compared to the 1st trimester.A significant linear positive correlation was found between BMI and 3rd trimester ADA, and a linear positive correlation between BMI and hs-CRP both in the 1st and 3rd trimester. The relationship between ∆ ADA and ∆ hs-CRP was non- significant. Conclusions: The observations of this study reveal increased inflammatory responses in obese pregnant women and suggests the importance of ADA and hs-CRP as early indicators of obesity-related complications prevailing thereafter, these markers can be useful for clinical diagnosis of impending maternal and neonatal complications.